Conference locations and sustainability aspirations. Towards an integrative framework? - Wenner, Fabian; Caset, Freke; Wit, Bart de (Taylor & Francis, 2019)
This paper addresses the sustainability of academic conferences in terms of their format and their choice of location(s). Environmental sustainability requires the minimisation of travel-related emissions, ideally through the consideration of geography in the location decision process and/or by adopting a multi-venue strategy. Social considerations command a fair distribution of advantages among academic association members in view of the monetary and non-monetary benefits that conferences convey to their host cities, universities and local researchers. This can, inter alia, be achieved through a rotation principle among members. From an economic standpoint, conferences are ideally large gatherings which allow for temporary agglomeration effects, and which should be easily accessible at low costs. Against this backdrop, this paper develops a conceptual framework in which the sustainability outcomes in terms of these format and location mechanisms are hypothesized. Following this, the framework is applied to the case of AESOP, the Association of European Schools of Planning, to explore to what extent this conference aligns with these considerations. It illustrates how AESOP qualifies as a rotating and predominantly dispersed single-venue conference, and consider to what extent its sustainability could be improved when other format and location strategies are adopted. We conclude the empirical section by making a case for more experimentation with, and research on, the multi-venue conference format, as it may represent the best option in balancing the three dimensions of sustainability. We argue that spatial planning and research organisations with sustainability aspirations may want to translate these goals more explicitly through their decisions on conference format and location.
Keywords: Wirtschaftsgeografie; Standort; Nachhaltigkeit; Verkehrskosten; Tagung; Kongress; Standortwahl; Wissenschaftler; Rotation; Räumliche Verteilung; Empirische Untersuchung